Legal Language in the Process of Law Enforcement Against Illegal Business in the Border Region of the Republic of Indonesia with the Democratic Republic of Timor Leste - I Gde Suranaya Pandit; I Nyoman Kardana; I Nyoman Sujana; Luh Made Mahendrawati; Simon Nahak; A.A. Rai Sita Laksmi; Pillipe Das Silva; Cesaltina Angela Soares; Acacio Fevucrules; Alarico Mendona Telman (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
This research is an empirical legal research because of the gap between the provisions and theories that exist with the legal facts that occur in society, about transactions of goods that cross the boundaries of a country has been regulated nationally by each country through certain procedures through the laws of the country -that. Against illegal business in the border area of the Republic of Indonesia with the Democratic Republic of East Timor, law enforcement must be carried out by law enforcement as an effort to harmonize concrete actualization with the applicable legal rules, with the national legal aspects of each country and agreed aspects of international law. The barriers and solutions to law enforcement against illegal business can be resolved through social and cultural, economic, political and security, while the solution that is used as an alternative is development in the border region specifically directed to accelerate the handling of the 3 fundamental problems faced by the border area, namely the delimitation aspect and Delineation of Boundaries, the aspect of affirming the national boundaries of the watershed area of the Republic of Indonesia with the State of Timor Leste, the aspect of the development gap is the fulfillment of economic infrastructure needs to foster opportunities for border areas to participate and compete in global markets and regional markets.